2020
DOI: 10.15252/embr.201948035
|View full text |Cite
|
Sign up to set email alerts
|

The p38‐interacting protein p38IP suppresses TCR and LPS signaling by targeting TAK1

Abstract: Negative regulation of immunoreceptor signaling is required for preventing hyperimmune activation and maintaining immune homeostasis. The roles of p38IP in immunoreceptor signaling remain unclear. Here, we show that p38IP suppresses T‐cell receptor (TCR)/LPS‐activated NF‐κB and p38 by targeting TAK1 kinase and that p38IP protein levels are downregulated in human PBMCs from rheumatoid arthritis (RA) patients, inversely correlating with the enhanced activity of NF‐κB and p38. Mechanistically, p38IP interacts wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 71 publications
(110 reference statements)
0
5
0
Order By: Relevance
“…A previous study identified the role of SP20H as a negative regulator controlling T cell receptor and LPS-activated NF-κB and p38 signaling in Jurkat T cells. 46 In line with this, activation of the TNF-p38 MAPK pathway is found in SP20H -knockout tumor cells, which is responsible for further induction of B7-H3 expression. Perhaps even more importantly, human eukaryotic translation initiation factor 4E (eIF4E), which interacts with eIF4A and eIF4G to assemble an active eIF4F complex that assumes cap-dependent translation, was characterized as a positive regulator of B7-H3 expression in our study.…”
Section: Discussionmentioning
confidence: 70%
“…A previous study identified the role of SP20H as a negative regulator controlling T cell receptor and LPS-activated NF-κB and p38 signaling in Jurkat T cells. 46 In line with this, activation of the TNF-p38 MAPK pathway is found in SP20H -knockout tumor cells, which is responsible for further induction of B7-H3 expression. Perhaps even more importantly, human eukaryotic translation initiation factor 4E (eIF4E), which interacts with eIF4A and eIF4G to assemble an active eIF4F complex that assumes cap-dependent translation, was characterized as a positive regulator of B7-H3 expression in our study.…”
Section: Discussionmentioning
confidence: 70%
“…Being responsible for the various distinct and even opposing fundamental cellular processes, the p38 cascade needs to be tightly regulated. Indeed, several regulatory mechanisms that determine the specificity of the cascade have been identified, including the duration and strength of the signals [ 13 , 14 ], which are controlled mainly by dual specificity phosphatases [ 15 , 16 ], scaffold proteins [ 17 ], and dynamic subcellular localization of the cascade’s components [ 18 ]. Importantly, the central roles of the cascade suggest that its dysregulation may cause various diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistically, p38IP dynamically interacts with TAK1 and promotes USP4-dependent deubiquitination of TAK1. Moreover, p38IP also inhibits the unanchored K63-linked ubiquitin chains binding to TAK1 (114). TAK1 activity can also be terminated by deubiquitinase cylindromatosis (Cyld) and E3 ubiquitin ligase Itch complex.…”
Section: Ubiquitination-mediated Regulation Of Tak1-tabs Signalosomementioning
confidence: 99%